PRODUK ORIGINAL EQUIPMENT MANUFACTURER (OEM) BERDASARKAN SUDUT PANDANG KONSUMEN - Hermanto Hermanto; Yunita Budi Rahayu Silintowe (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2018)
One of the company’s efforts to reduce operating costs, the speed of product delivery time, and improve product quality is by producing OEM products. OEM products are expected to play a critical role in the market and control the range of competitive values of product sales. The purpose of this research is to explain consumer perception of price, quality, and packaging of Original Equipment Manufacturer (OEM) product printer spare parts in Karunia Toner store. Consumer perception data using primary data obtained by using in-depth interview technique. As research subjects are consumers, who have purchased an OEM product at the Karunia Toner store. As the factors of perception include price, quality, and product packaging. Data analysis using qualitative descriptive analysis technique with data collection stage, data reduction, conclusion drawing and display data. The results show that consumer perception when viewed from the quality, OEM products have less good quality; from the price aspect, OEM products have low prices, resulting in a negative perception for consumers; while from packaging, OEM product packaging is also considered less attractive, the size is too small and the packaging image is simple, and the quality of packaging is also less good. Consumer perceptions of OEM printer spare part products are not good enough in the eyes of consumers.